Effects of antibacterial peptide-producing Bacillus subtilis, gallic acid, and cellulase on fermentation quality and bacterial community of whole-plant corn silage - Zhang, Zhiheng; Wang, Yuqin; Wang, Saiqiao; Zhao, Lu; Zhang, Binglei; Jia, Wanhang; Zhai, Zhenhan; Zhao, Lingping; Li, Yuanxiao (Frontiers in Microbiology, 2022)
In the current study, we assessed the effects of antibacterial peptide-producing Bacillus subtilis(BS), Gallic acid(GA) and Cellulase(CL) on the fermentation quality and bacterial community of various varieties of whole-plant corn silage. Three different varieties of whole-plant corn (Yuqing386, Enxiai298 and Nonghe35) were treated with 0.02% BS (fresh material basis), 0.2% GA (fresh material basis) and 0.02% CL (fresh material basis), after which 45 days of anaerobic fermentation were conducted. With the exception of its low dry matter content, the results showed that Yuqing386's crude protein, water-soluble carbohydrate, and lactic acid contents were significantly higher than those of the other two corn varieties. However, its acid detergent fiber and cellulose contents were significantly lower than those of the other two corn varieties. Among the three corn variety silages, Yuqing386 had the highest relative abundance of Lactobacillus at the genus level and the biggest relative abundance of Firmicutes at the phylum level. In addition, the three additives markedly enhanced the quantity of dry matter and crude protein as compared to the control group. The application of GA considerably decreased the level of neutral detergent fiber while significantly increasing the content of lactic acid and water-soluble carbohydrates. Even though all additives enhanced the structure of the bacterial community following silage, the GA group experienced the greatest enhancement. On a phylum and genus level, the GA group contains the highest relative abundance of Firmicutes and Lactobacillus, respectively. Overall, of the three corn varieties, Yuqing386 provides the best silage qualities. GA has the biggest impact among the additions employed in this experiment to enhance the nutritional preservation and fermentation quality of whole-plant corn silage.